The impact of the Corona pandemic (Covid- 19) on contracts and financial obligations in Saudi Arabia - AL.Azzam, Saad Nasser (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to identify the effects of contracts and financial obligations in light of the Covid- 19 pandemic, as one of the contracts most affected by the Covid- 19 epidemic is the financial contracts necessary for both parties, and lax implementation, and the impact may be easy, and it may be such as force majeure and emergency conditions. Which causes fatigue, exhaustion and losses for both parties to the contract, but it is possible to continue implementing the contract if the judge takes his interest, and he can give the obligor a respite if he finds that the emergency circumstance is subject to lapse and termination within a short time that does not harm the obligor to him. The value of the obligation can be adjusted in order to remove the damage and the emergency circumstance, and since the pandemic is one of the force majeure circumstances and the contract cannot continue with it, here the contract is terminated, and the joint wage for work in the custodianship is excluded and did not stipulate the worker’s appointment, so he must take his place if he is unable to work And if there is a delay in the contract due to the pandemic , it is not valid to impose a fine for the delay at that time. The study recommended the need to increase the education and awareness of society, especially traders, brokers, and those engaged in trade, as well as the civil society that contracts with these groups.